The frequency of complications in a cohort of patients diagnosed with hemophilia A and hemophilia B receiving prophylactic treatment in Colombia: A retrospective noninterventional study. - Jorge E Machado Alba; Juan David Wilches-Gutierrez; Diana Rocio Arias-Osorio; Juan Manuel Reyes; Maria Lourdes Nakandakari; Harrison David Ospina-Arzuaga; Andres Gaviria-Mendoza; Natalia Castaño-Gamboa; Luis Fernando Valladales-Restrepo; Manuel E Machado-Duque (PLoS ONE, 2023)
Introduction Hemophilia A and B are disorders associated with the deficit of coagulation factors VIII and IX. Objective Was to determine the incidence of complications in a cohort of patients diagnosed with moderate and severe hemophilia A or B under treatment in a specialized institution. Methods A retrospective study of a cohort of patients with replacement therapy for hemophilia A or B, evaluating treatment and complications between January/2012 and July/2019. Sociodemographic, clinical and disease management-related variables were extracted from the medical records. Time to inhibitor development and rate associated with bleeding and hospitalizations were evaluated. Results A total of 159 male patients were identified with hemophilia A (n = 140; 88.1%) and B (n = 19; 11.9%) with a mean follow-up of 5.9±2.3 years. The mean age was 23.6±16.1 years, hemophilia was reported as severe in 125 patients in hemophilia A (89.3%) and 13 patients in hemophilia B (68.4%). Primary prophylaxis was registered in 17.0% of patients, 44.7% secondary, and 38.3% tertiary, with recombinant factors (n = 84; 52.8%) followed by plasma derived factors (n = 75; 47.2%). The incidence of inhibitor development was 0.3 per 100 patients/year, with mean time to event of 509 days. The incidence of bleeding was 192 per 100 patients/year, especially at the joint (n = 99; 62.3%) and muscle (n = 25; 15.7%) level. The incidence of hospitalization was 3.7 per 100 patients/year. Conclusions The most common complication was joint bleeding which was expected in this type of patients. Low proportion of patients developed factor inhibitors during the follow up.